Production process of protection tube with bi-component insulation paste

By wrapping the opposite aramid fiber and carbon fiber braided layer on the casing and coating the two-component fixing glue, the problem of existing casing materials being prone to aging and brittle in harsh environments is solved, and the casing is improved Effects of pressure resistance, corrosion resistance, wear resistance and insulation performance.

CN119408202APending Publication Date: 2025-02-11衡诚能源科技(上海)有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411509912.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11

Smart Images

  • Figure CN119408202A_ABST
    Figure CN119408202A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of power cables, in particular to a protection tube production process, which comprises the following steps of: (1) weaving and winding anisotropic aramid fibers on the outer wall of a sleeve; (2) carbon fibers are woven and wound on the heterogenous aramid fiber woven layer; (3) the sleeve wound with the anisotropic aramid fiber woven layer and the carbon fiber woven layer is put into a curing oven to be heated and cured; (4) polishing and cleaning the sleeve wound with the anisotropic aramid fiber braid layer and the carbon fiber braid layer; (5) the carbon fiber woven layer is coated with fixing glue, the fixing glue is composed of two components, the carbon fiber woven layer is coated with the first component, and the second component is evenly sprayed on the coating of the first component; the first component is also doped with a fragment-shaped glass fiber net, and the fragment-shaped glass fiber net is used as a filler; and (6) the fixing glue is subjected to curing treatment, the curing temperature is controlled to be 25-45 DEG C, and the curing time is 20-30 hours under the pressure of 0.1-0.2 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of power cables, and in particular to a production process of a protection tube. Background Art

[0002] Traditional materials for casings are generally CPVC and PVC. Such casings are prone to aging and embrittlement under harsh environments such as long-term ultraviolet radiation, temperature changes, and chemical corrosion, resulting in a decrease in mechanical strength, thereby increasing maintenance costs and safety risks. In addition, PVC materials have poor impact resistance. Once impacted by external forces, they are prone to breakage, and the repair process is cumbersome and time-consuming. In densely populated areas such as residential areas, damage to power pipes and casings not only affects the daily lives of residents, but may also cause electric shock accidents, resulting in casualties and property losses. Damage to underground pipelines may also affect other underground facilities, such as water supply and gas supply, leading to wider service interruptions.

[0003] In order to solve these problems, a protective tube production process is needed to improve the pressure resistance, corrosion resistance, wear resistance and insulation performance of the casing. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract of the specification and the title of the invention of this application to avoid blurring the purpose of this section, the abstract of the specification and the title of the invention, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems existing in the prior art, the present invention is proposed.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The production process of the protective tube with two-component insulating adhesive is to prepare the casing first.

[0008] Step (1) fixing the sleeve, and weaving and winding the heteroaramid fibers on the outer wall of the sleeve at a fixed weaving angle to form a heteroaramid braided layer;

[0009] Step (2) weaving and winding the carbon fiber on the heteroaramid braided layer at a fixed braiding angle to form a carbon fiber braided layer;

[0010] Step (3) After the carbon fiber braided layer is wound, the sleeve wound with the heteroaramid braided layer and the carbon fiber braided layer is placed in a curing furnace for heating and curing;

[0011] Step (4) After the curing of the heteroaramid braided layer and the carbon fiber braided layer is completed, the sleeve wrapped with the heteroaramid braided layer and the carbon fiber braided layer is polished and cleaned;

[0012] Step (5) coating a fixing glue on the carbon fiber braided layer, wherein the fixing glue is a two-component fixing glue, wherein the two components are a first component and a second component, the first component is coated on the carbon fiber braided layer, and the second component is evenly sprayed on the first component coating;

[0013] In terms of weight percentage, the first component includes 19%-31% of polydimethylsiloxane, 19%-31% of methyltriethoxysilane, 8%-9.5% of white carbon black and 5%-6% of tetraethoxysilane, which are uniformly mixed. The first component is also doped with fragmented glass fiber mesh, which is used as filler.

[0014] The glass fiber mesh includes a mesh body and expanded glass fibers, the mesh body is woven with warp and weft, and both the warp and weft are made of glass fibers;

[0015] The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers;

[0016] The second component includes 1%-2% of catalyst, 8%-9% of accelerator, and 6%-7% of tackifier, which are uniformly mixed;

[0017] Step (6) solidifies the fixing glue, controls the curing temperature to be 25-45° C., and the curing time to be 20-30 hours at 0.1-0.2 MPa.

[0018] Through the above process, a sleeve wrapped with anisoaramid braided layer and a carbon fiber braided layer is produced by organic combination, and the anisoaramid braided layer, the carbon fiber braided layer and the sleeve outer wall are fixed together with a fixing glue coated on the carbon fiber braided layer to form a reinforced structure.

[0019] Wherein, a structural layer of anisotropic aramid braided layer and carbon fiber braided layer is wrapped in the casing through steps (1), (2) and (3). Aramid is a high-performance fiber with extremely high strength and heat resistance, while carbon fiber is known for its excellent mechanical properties and light weight. The casing not only has excellent mechanical properties, but also has good insulation and corrosion resistance. The anisotropic aramid braided layer and carbon fiber braided layer can also effectively block sunlight and extend the service life of the casing of CPVC or PVC materials. Due to the high strength and impact resistance of the casing of the anisotropic aramid braided layer and carbon fiber braided layer, the protective tube is not easily damaged during transportation and installation, reducing the loss during the construction process. While ensuring that the number of fiber meshes is moderate, it is ensured that the expanded glass fibers are interlaced as much as possible to form a three-dimensional mesh structure to improve the overall strength.

[0020] Through step (4), the sleeve wrapped with the heteroaramid braided layer and the carbon fiber braided layer is polished and cleaned to prepare for the uniformity and bonding effect of the subsequent fixing glue.

[0021] The fixing glue applied to the carbon fiber braided layer in step (5) and step (6) forms an adhesive layer. The adhesive layer can not only ensure that the heteroaramid and carbon fiber are tightly bonded to the sleeve of CPVC or PVC material, but also absorb impact energy to a certain extent, thereby improving the impact resistance of the pipe.

[0022] By doping the glass fiber mesh in step (5), the glass fiber mesh retains expanded glass fibers. The beneficial effect of the expanded glass fibers is that while ensuring that the amount of the fiber mesh is moderate, the expanded glass fibers are staggered as much as possible to form a three-dimensional network structure, thereby improving the overall strength.

[0023] The fixing glue adopts a fixing glue of two components. Through condensation reaction (condensation reaction is a reaction in which two or more organic molecules interact with each other and are combined into a macromolecule by covalent bonds, and are often accompanied by the loss of small molecules such as water, hydrogen chloride, alcohol, etc.), a strong chemical bond can be formed, so that the fixing glue has excellent adhesion and structural strength when connecting materials. Tetraethoxysilane is a cross-linking agent, also known as a bridging agent, which can form silicone polymers through hydrolysis and condensation reactions. These polymers can be cross-linked under ultraviolet light to form a strong network structure, so that the fixing glue has a photocuring effect. White carbon black has a good thickening effect and can increase the viscosity of the fixing glue. Adding white carbon black can enhance the mechanical strength of the fixing glue and improve the firmness of the bonding. Especially after the fixing glue is cured, white carbon black can provide additional support as a filling material.

[0024] The two-component fixing glue has the characteristics of rapid curing, and can complete the repair work in a short time, which greatly shortens the maintenance time and reduces the impact on traffic and residents' lives. The fixing glue also has good waterproof and chemical corrosion resistance, which further improves the service life and reliability of the protective pipe. At the same time, due to its excellent repair performance, even in the event of local damage, local repairs can be carried out quickly without replacing the entire section of the pipeline, thereby reducing maintenance costs.

[0025] Preferably, the glass fiber woven mesh with a diameter of 6.5-9.5μm has good softness and certain toughness; the area of ​​the mesh is 0.5-2mm2, and the formed fragmented glass fiber mesh is not easy to tangle into balls after being doped into the polymer moisture-proof sealing glue as a filler, and the mesh area is 0.01-0.19mm2, allowing the silicone base material to pass through the mesh and combine with the fiber mesh more strongly; the length of the extended glass fiber is 0.5-2mm, and in terms of volume, there are 2-5 glass fiber meshes per unit cubic centimeter, ensuring that the extended glass fibers are interlaced as much as possible to form a three-dimensional mesh structure.

[0026] Preferably, the catalyst in the second component is dibutyltin dilaurate, the accelerator is γ-aminopropyltriethoxysilane, and the tackifier is N-β-aminoethyl-γ-aminopropyltrimethoxysilane. The rate of the condensation reaction can be adjusted by the second component, making the production process more flexible. The catalyst is dibutyltin dilaurate, and the accelerator is γ-aminopropyltriethoxysilane, which is a substance that can accelerate the chemical reaction rate without being consumed in the reaction. The tackifier is N-β-aminoethyl-γ-aminopropyltrimethoxysilane, which can help fix the glue to shape.

[0027] Preferably, in step (5), the production method of the glass fiber mesh comprises the following steps: (1) when drawing the glass fiber as one of the warp and weft, in a molten state, through a space where ferroferric oxide powder dust floats in the air, soft magnetic powder is bonded, and the particle size of the soft magnetic powder is 0.05-0.20 μm; (2) when drawing the glass fiber as the other of the warp and weft, in a molten state, through a space where ferroferric oxide powder dust floats in the air, graphite powder is bonded, and the particles of the graphite powder are 6-10 μm; the glass fiber is strong and uniform, without adhesive, and will not cause structural damage at high and low temperatures, thereby ensuring the long-lasting bonding strength between the glass fiber and the silicone base material. And it can withstand electromagnetic induction heating at higher temperatures.

[0028] Furthermore, 1%-2% of graphene oxide-europium oxide composite is added to the first component of the fixing glue.

[0029] In step (6), the fixing glue is auxiliary-cured by an auxiliary curing device;

[0030] The auxiliary curing device includes an electromagnet, an oscillating circuit connected to the electromagnet to generate a magnetic field with periodic direction changes, and the electromagnet is close to the fixing glue; the soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the curing glue. While vibrating, it also promotes the tightness of the glass fiber and the fixing glue, so that the fixing glue mixed with the graphene oxide-europium oxide composite forms a conductive fluid.

[0031] The auxiliary curing device also includes an electromagnetic emitter, and the europium oxide in the graphene oxide-europium oxide composite is excited to fluoresce through the electromagnetic field generated by the electromagnetic emitter.

[0032] Tetraethoxysilane is a cross-linking agent, also known as a bridging agent, which can form silicon-oxygen polymers through hydrolysis and condensation reactions. These polymers can be cross-linked under ultraviolet light to form a solid network structure, making the fixed glue have a photocuring effect. When the first component is excited to fluoresce by the electromagnetic field generated by the electromagnetic emitter through europium oxide, it cross-links under fluorescence irradiation to form a cured structure. The coating surface of the first component undergoes a condensation reaction with the second component to form a coating layer. This fixed glue that combines light curing and chemical condensation can improve the performance and durability of the cured fixed glue.

[0033] The auxiliary curing equipment also includes a microwave heating device, which generates an alternating magnetic field, and the fixing glue is heated and cured by the microwave heating device.

[0034] Beneficial effect: the heteroaramid braided layer and the carbon fiber braided layer are cured by microwave heating; microwave heating curing uses microwaves generated by a microwave heating device to produce rapid molecular movement in the material, thereby rapidly heating the material. Microwaves can directly generate heat inside the material, unlike traditional heating that requires heat conduction. The heteroaramid braided layer and the carbon fiber can be heated and shaped efficiently and quickly, reducing thermal gradients and local overheating, thereby improving the overall quality of the product and ensuring that the overall structure of the protective tube will not be damaged during heating.

[0035] The heteroaramid braided layer and the carbon fiber braided layer are cured by microwave heating, polished and cleaned, and then coated with a fixing glue, which is then cured by microwave heating.

[0036] Glass fiber is bonded with soft magnetic powder. Soft magnetic powder has soft magnetic properties, which can introduce the magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties heat relatively evenly.

[0037] Preferably, the fiber braiding angle of the carbon fiber braided layer in step (2) is different from the fiber braiding angle of the heteroaramid braided layer; by optimizing the local winding method of the carbon fiber braided layer in step (2), it is ensured that each layer of material of the protective tube is evenly stressed during the production process, avoiding the generation of stress concentration areas, thereby improving the overall performance and structural strength of the casing. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0039] Figure 1 It is a schematic cross-sectional structural diagram of a protection tube with a two-component insulating adhesive according to the present invention;

[0040] Figure 2 It is a schematic diagram of the structural principle of the glass fiber mesh of the present invention;

[0041] Figure 3 This is a microscopic display of the glass fiber mesh of the present invention. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned objects, features and advantages of the present invention more understandable, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.

[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0044] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0045] Furthermore, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in less than one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0046] refer to Figure 1 and Figure 2 , a production process of a protective tube with a two-component insulating adhesive, first preparing a casing 1.

[0047] Step (1) fixing the sleeve 1, and weaving and winding the heteroaramid fibers on the outer wall of the sleeve 1 at a fixed weaving angle to form a heteroaramid braided layer 2;

[0048] Step (2) weaving and winding the carbon fiber on the heteroaramid braided layer 2 at a fixed braiding angle to form a carbon fiber braided layer 3;

[0049] Step (3) After the carbon fiber braided layer 3 is wound, the sleeve 1 wound with the heteroaramid braided layer 2 and the carbon fiber braided layer 3 is placed in a curing furnace for heating and curing;

[0050] Step (4) After the curing of the anisoaramid braided layer 2 and the carbon fiber braided layer 3 is completed, the sleeve 1 wound with the anisoaramid braided layer 2 and the carbon fiber braided layer 3 is polished and cleaned;

[0051] Step (5) coating a fixing glue on the carbon fiber braided layer 3, wherein the fixing glue is a two-component fixing glue, wherein the two components are a first component and a second component, the first component is coated on the carbon fiber braided layer 3, and the second component is evenly sprayed on the first component coating;

[0052] In terms of weight percentage, the first component includes 19%-31% of polydimethylsiloxane, 19%-31% of methyltriethoxysilane, 8%-9.5% of white carbon black and 5%-6% of tetraethoxysilane, which are uniformly mixed. The first component is also doped with a fragmented glass fiber mesh 4, and the fragmented glass fiber mesh 4 is used as a filler.

[0053] The glass fiber mesh 4 includes a mesh body 41 and extended glass fibers 42. The mesh body 41 is woven with warp and weft threads, and both the warp and weft threads are made of glass fibers.

[0054] The lengths of at least part of the warp threads and at least part of the weft threads are both beyond the mesh body 41, forming extended glass fibers 42;

[0055] The second component includes 1%-2% of catalyst, 8%-9% of accelerator, and 6%-7% of tackifier, which are uniformly mixed;

[0056] Step (6) solidifies the fixing glue, controls the curing temperature to be 25-45° C., and the curing time to be 20-30 hours at 0.1-0.2 MPa.

[0057] Through the above process, the sleeve 1 wrapped with the heteroaramid braided layer 2 and the carbon fiber braided layer 3 is produced by organic combination, and the fixing glue coated on the carbon fiber braided layer 3 is used to fix the heteroaramid braided layer 2, the carbon fiber braided layer 3 and the outer wall of the sleeve 1 to form a reinforced structure.

[0058] Wherein, the structural layer of the heteroaramid braided layer 2 and the carbon fiber braided layer 3 is wrapped in the sleeve 1 through steps (1), (2) and (3). Aramid is a high-performance fiber with extremely high strength and heat resistance, while carbon fiber is known for its excellent mechanical properties and light weight. The sleeve 1 not only has excellent mechanical properties, but also has good insulation and corrosion resistance. The heteroaramid braided layer 2 and the carbon fiber braided layer 3 can also effectively block sunlight and extend the service life of the sleeve 1 made of CPVC or PVC material. Due to the high strength and impact resistance of the sleeve 1 of the heteroaramid braided layer 2 and the carbon fiber braided layer 3, the protective tube is not easily damaged during transportation and installation, reducing the loss during the construction process. While ensuring that the number of fiber meshes is moderate, it is ensured that the expanded glass fibers 42 are interlaced as much as possible to form a three-dimensional mesh structure to improve the overall strength.

[0059] Through step (4), the sleeve 1 wound with the heteroaramid braided layer 2 and the carbon fiber braided layer 3 is polished and cleaned to prepare for the uniformity and bonding effect of the subsequent fixing glue.

[0060] The fixing glue applied to the carbon fiber braided layer 3 in step (5) and step (6) forms an adhesive layer. The adhesive layer can not only ensure that the heteroaramid and carbon fiber are tightly combined with the sleeve 1 of CPVC or PVC material, but also absorb impact energy to a certain extent, thereby improving the impact resistance of the pipe.

[0061] By doping the glass fiber mesh 4 in step (5), the glass fiber mesh 4 retains the expanded glass fibers 42. The beneficial effect of the expanded glass fibers 42 is that while ensuring that the number of fiber meshes is moderate, the expanded glass fibers 42 are staggered as much as possible to form a three-dimensional network structure, thereby improving the overall strength.

[0062] The fixing glue adopts a fixing glue of two components. Through condensation reaction (condensation reaction is a reaction in which two or more organic molecules interact with each other and are combined into a macromolecule by covalent bonds, and are often accompanied by the loss of small molecules such as water, hydrogen chloride, alcohol, etc.), a strong chemical bond can be formed, so that the fixing glue has excellent adhesion and structural strength when connecting materials. Tetraethoxysilane is a cross-linking agent, also known as a bridging agent, which can form silicone polymers through hydrolysis and condensation reactions. These polymers can be cross-linked under ultraviolet light to form a strong network structure, so that the fixing glue has a photocuring effect. White carbon black has a good thickening effect and can increase the viscosity of the fixing glue. Adding white carbon black can enhance the mechanical strength of the fixing glue and improve the firmness of the bonding. Especially after the fixing glue is cured, white carbon black can provide additional support as a filling material.

[0063] The two-component fixing glue has the characteristics of rapid curing, and can complete the repair work in a short time, which greatly shortens the maintenance time and reduces the impact on traffic and residents' lives. The fixing glue also has good waterproof and chemical corrosion resistance, which further improves the service life and reliability of the protective pipe. At the same time, due to its excellent repair performance, even in the event of local damage, local repairs can be carried out quickly without replacing the entire section of the pipeline, thereby reducing maintenance costs.

[0064] Preferably, the glass fiber woven mesh with a diameter of 6.5-9.5μm has good softness and certain toughness; the area of ​​the mesh body 41 is 0.5-2mm2, and the fragmented glass fiber mesh 4 formed is not easy to tangle into a ball after being doped into the polymer moisture-proof sealing glue as a filler, and the mesh area is 0.01-0.19mm2, allowing the silicone base material to pass through the mesh and the bonding strength with the fiber mesh is stronger; the length of the extended glass fiber 42 is 0.5-2mm, and in terms of volume, there are 2-5 glass fiber meshes 4 per unit cubic centimeter, ensuring that the extended glass fibers 42 are interlaced as much as possible to form a three-dimensional mesh structure.

[0065] Preferably, the catalyst in the second component is dibutyltin dilaurate, the accelerator is γ-aminopropyltriethoxysilane, and the tackifier is N-β-aminoethyl-γ-aminopropyltrimethoxysilane. The rate of the condensation reaction can be adjusted by the second component, making the production process more flexible. The catalyst is dibutyltin dilaurate, and the accelerator is γ-aminopropyltriethoxysilane, which is a substance that can accelerate the chemical reaction rate without being consumed in the reaction. The tackifier is N-β-aminoethyl-γ-aminopropyltrimethoxysilane, which can help fix the glue to shape.

[0066] Preferably, in step (5), the production method of the glass fiber mesh 4 is as follows: (1) when drawing the glass fiber as one of the warp and weft, in a molten state, through a space where ferroferric oxide powder dust floats in the air, soft magnetic powder is bonded, and the particle size of the soft magnetic powder is 0.05-0.20 μm; (2) when drawing the glass fiber as the other of the warp and weft, in a molten state, through a space where ferroferric oxide powder dust floats in the air, graphite powder is bonded, and the particles of the graphite powder are 6-10 μm; the glass fiber is strong and uniform, without adhesive, and will not cause structural damage at high and low temperatures, ensuring the long-lasting bonding strength between the glass fiber and the silicone base material. And it can withstand electromagnetic induction heating at higher temperatures.

[0067] Furthermore, 1%-2% of graphene oxide-europium oxide composite is added to the first component of the fixing glue.

[0068] In step (6), the fixing glue is auxiliary-cured by an auxiliary curing device;

[0069] The auxiliary curing device includes an electromagnet, an oscillating circuit connected to the electromagnet to generate a magnetic field with periodic direction changes, and the electromagnet is close to the fixing glue; the soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the curing glue. While vibrating, it also promotes the tightness of the glass fiber and the fixing glue, so that the fixing glue mixed with the graphene oxide-europium oxide composite forms a conductive fluid.

[0070] The auxiliary curing device also includes an electromagnetic emitter, and the europium oxide in the graphene oxide-europium oxide composite is excited to fluoresce through the electromagnetic field generated by the electromagnetic emitter.

[0071] Tetraethoxysilane is a cross-linking agent, also known as a bridging agent, which can form silicon-oxygen polymers through hydrolysis and condensation reactions. These polymers can be cross-linked under ultraviolet light to form a solid network structure, making the fixed glue have a photocuring effect. When the first component is excited to fluoresce by the electromagnetic field generated by the electromagnetic emitter through europium oxide, it cross-links under fluorescence irradiation to form a cured structure. The coating surface of the first component undergoes a condensation reaction with the second component to form a coating layer. This fixed glue that combines light curing and chemical condensation can improve the performance and durability of the cured fixed glue.

[0072] The auxiliary curing equipment also includes a microwave heating device, which generates an alternating magnetic field, and the fixing glue is heated and cured by the microwave heating device.

[0073] Beneficial effect: the heteroaramid braided layer 2 and the carbon fiber braided layer 3 are cured by microwave heating; microwave heating curing uses microwaves generated by a microwave heating device to produce rapid molecular movement in the material, thereby rapidly heating the material. Microwaves can directly generate heat inside the material, unlike traditional heating that requires heat conduction. The heteroaramid braided layer 2 and the carbon fiber can be heated and shaped efficiently and quickly, reducing thermal gradients and local overheating, thereby improving the overall quality of the product and ensuring that the overall structure of the protective tube will not be damaged during heating.

[0074] The heteroaramid braided layer 2 and the carbon fiber braided layer 3 are cured by microwave heating, polished and cleaned, and then coated with a fixing glue, which is cured by microwave heating.

[0075] Glass fiber is bonded with soft magnetic powder. Soft magnetic powder has soft magnetic properties, which can introduce the magnetic field deep into the fluid glue, forming a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties heat relatively evenly.

[0076] Preferably, the fiber braiding angle of the carbon fiber braided layer 3 in step (2) is different from the fiber braiding angle of the heteroaramid braided layer 2; by optimizing the local winding method of the carbon fiber braided layer 3 in step (2), it is ensured that each layer of material of the protective tube is evenly stressed during the production process, avoiding the generation of stress concentration areas, thereby improving the overall performance and structural strength of the sleeve 1.

[0077] Embodiment 1:

[0078] The first component: 100 parts of polydimethylsiloxane, 100 parts of methyltriethoxysilane, 30 parts of white carbon black, and 15 parts of tetraethoxysilane.

[0079] The second component: 5 parts of dibutyltin dilaurate, 30 parts of γ-aminopropyltriethoxysilane, and 20 parts of N-β-aminoethyl-γ-aminopropyltrimethoxysilane.

[0080] Coating conditions: room temperature 25°C, 0.1MPa, curing time 24 hours (the macromolecules react chemically with the cross-linking agent - tetraethoxysilane under heating, cross-linking to form a three-dimensional network structure, and the first component and the second component of the fixing glue undergo condensation reaction to form a room temperature curing silicone rubber coating. This process combines light curing and chemical cross-linking to improve the performance and durability of the material).

[0081] Performance test: insulation resistance>10 12 Ω·cm, compressive strength>50MPa, wear resistance>100,000 times.

[0082] Embodiment 2:

[0083] The first component: 105 parts of polydimethylsiloxane, 110 parts of methyltriethoxysilane, 30 parts of white carbon black, and 15 parts of tetramethoxysilane.

[0084] The second component: 5 parts of dibutyltin dilaurate, 30 parts of γ-aminopropyltriethoxysilane, and 25 parts of N-β-aminoethyl-γ-aminopropyltrimethoxysilane.

[0085] Coating conditions: temperature 35°C, 0.2MPa, curing time 24 hours.

[0086] Performance test: insulation resistance>10 12 Ω·cm, compressive strength>50MPa, wear resistance>100,000 times.

[0087] Embodiment 3:

[0088] The first component: 100 parts of polydimethylsiloxane, 118 parts of methyltriethoxysilane, 25 parts of white carbon black, and 15 parts of tetramethoxysilane.

[0089] The second component: 5 parts of dibutyltin dilaurate, 30 parts of γ-aminopropyltriethoxysilane, and 25 parts of N-β-aminoethyl-γ-aminopropyltrimethoxysilane.

[0090] Coating conditions: The temperature was adjusted to 40°C, 0.1MPa, and the curing time was shortened to 20 hours.

[0091] Performance test: insulation resistance>10 12 Ω·cm, compressive strength>50MPa, wear resistance>100,000 times.

[0092] Embodiment 4:

[0093] The first component: 100 parts of polydimethylsiloxane, 120 parts of methyltriethoxysilane, 25 parts of white carbon black, and 18 parts of dimethyldiethoxysilane.

[0094] The second component: 3 parts of dioctyltin dilaurate, 28 parts of γ-aminopropyltriethoxysilane, and 20 parts of glycidoxypropyltriethoxysilane.

[0095] Coating conditions: The temperature was set at 30 °C, 0.1 MPa, and the curing time was extended to 48 h to ensure that the cured fixing glue was completely cured.

[0096] Performance test: In addition to the conventional insulation resistivity, compressive strength and wear resistance tests, the insulation resistivity test of the manufactured protection tube showed that its insulation performance was significantly improved. The compressive strength test was also carried out, and it was found that it could withstand higher pressure without breaking. The wear resistance test showed that the protection tube exhibited excellent wear resistance in the wear test under simulated harsh environment.

[0097] Embodiment 5:

[0098] The first component: 115 parts of polydimethylsiloxane, 105 parts of methyltriethoxysilane, 35 parts of white carbon black, and 12 parts of tetrapropoxysilane.

[0099] The second component: 7 parts of dibutyltin dilaurate, 35 parts of γ-aminopropyltrimethoxysilane, and 22 parts of N-β-aminoethyl-γ-aminopropyltriethoxysilane.

[0100] Coating conditions: temperature raised to 45°C, 0.2MPa, and curing time maintained at 24 hours.

[0101] Performance test: In addition to the conventional insulation resistivity, compressive strength and wear resistance tests, the bonding strength between the cured adhesive and the substrate was also tested. The results showed that the cured adhesive was tightly bonded to the substrate without any falling off.

[0102] Embodiment 6:

[0103] First component: 5 parts of graphene oxide-europium oxide complex are added to the first component. The remaining components are: 110 parts of polydimethylsiloxane, 110 parts of methyltriethoxysilane, 30 parts of white carbon black, and 15 parts of dimethyldiethoxysilane.

[0104] The second component: 5 parts of dibutyltin dilaurate, 30 parts of γ-aminopropyltriethoxysilane, and 25 parts of N-β-aminoethyl-γ-aminopropyltrimethoxysilane.

[0105] Coating conditions: temperature set at 38°C, 0.1MPa, and curing time of 26 hours.

[0106] Performance test: On the basis of conventional performance test, special attention was paid to the stability of the cured fixing glue in high temperature environment. After high temperature aging test (150℃, lasting 72 hours), the cured fixing glue showed no obvious signs of aging and maintained excellent insulation performance and mechanical strength. In addition, flame retardant performance test was also carried out, and the results showed that the protective tube has good flame retardant performance.

[0107] The above examples show different material combinations and ratios, aiming to demonstrate the flexibility and wide application potential of the present invention. Through Example 1, Example 2, and Example 3, after adjusting the ratio, the material performance can achieve an insulation resistivity of >10 12 Ω·cm, compressive strength>50MPa, wear resistance>100,000 times, but the rise in temperature can effectively shorten the curing time (the temperature is higher than the normal temperature, the production difficulty increases). According to Example 4, it can be measured that the curing is sufficient, and the insulation performance, compressive strength and wear resistance of the protective tube are better; the curing time can be effectively shortened under heating and pressurization. Example 6 adds 5 parts of graphene oxide-europium oxide composite to accurately control the heating rate of conductive graphite powder, thereby controlling the efficiency and speed of curing. Moreover, europium oxide can excite fluorescence through an alternating magnetic field, and tetraethoxysilane can be photocured. The heating method is simple, and the fixing glue can be cured within 26 hours under normal pressure. The production method is simple and fast enough.

[0108] In Example 6, the fixing glue in the gap between the heteroaramid braided layer 2 and the carbon fiber braided layer 3 can be fixed by exciting the fluorescence of europium oxide through an electromagnetic field. Tetraethoxysilane is first photocured to shape the curing glue, and then the first component and the second component of the fixing glue undergo a condensation reaction to form a coating layer of the cured fixing glue. This fixing glue curing structure that combines photocuring and chemical condensation can improve the performance and durability of the cured fixing glue.

[0109] Importantly, it should be noted that the construction and arrangement of the present application shown in a number of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible, for example, the size, scale, structure, shape and proportion of various elements, and parameter values ​​such as temperature, pressure, etc., mounting arrangements, use of materials, color, directional changes, etc., without substantially departing from the novel angles and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of the execution function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other substitutions, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.

[0110] Furthermore, in order to provide a concise description of exemplary embodiments, all features of the actual embodiment may not be described, namely those features that are not relevant to the best mode presently contemplated for carrying out the invention or those features that are not relevant to implementing the invention.

[0111] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, the development effort will be a routine task of design, fabrication, and production without undue experimentation.

[0112] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A production process for a protective tube with a two-component insulating adhesive, first preparing a casing, characterized in that: The following steps are involved: Step (1) fixing the sleeve, and weaving and winding the heteroaramid fibers on the outer wall of the sleeve at a fixed weaving angle to form a heteroaramid braided layer; Step (2) weaving and winding the carbon fiber on the heteroaramid braided layer at a fixed braiding angle to form a carbon fiber braided layer; Step (3) After the carbon fiber braided layer is wound, the sleeve wound with the heteroaramid braided layer and the carbon fiber braided layer is placed in a curing furnace for heating and curing; Step (4) After the curing of the anisotropic aramid braided layer and the carbon fiber braided layer is completed, the sleeve wrapped with the anisotropic aramid braided layer and the carbon fiber braided layer is polished and cleaned; Step (5) coating a fixing glue on the carbon fiber braided layer, wherein the fixing glue is a two-component fixing glue, wherein the two components are a first component and a second component, the first component is coated on the carbon fiber braided layer, and the second component is evenly sprayed on the first component coating; In terms of weight percentage, the first component includes 19%-31% of polydimethylsiloxane, 19%-31% of methyltriethoxysilane, 8%-9.5% of white carbon black and 5%-6% of tetraethoxysilane, which are uniformly mixed. The first component is also doped with fragmented glass fiber mesh, which is used as filler. The glass fiber mesh includes a mesh body and expanded glass fibers, the mesh body is woven with warp and weft, and both the warp and weft are made of glass fibers; The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers; The second component includes 1%-2% of catalyst, 8%-9% of accelerator, and 6%-7% of tackifier, which are uniformly mixed; Step (6) solidifies the fixing glue, controls the curing temperature to be 25-45° C., and the curing time to be 20-30 hours at 0.1-0.2 MPa.

2. The production process of the protective tube with two-component insulating adhesive according to claim 1 is characterized in that: The diameter of the glass fibers of the glass fiber mesh is 6.5-9.5 μm; The area of ​​the mesh is 0.5-2mm 2 , mesh area is 0.01-0.19mm 2 ; The length of the expanded glass fiber is 0.5-2mm; Measured by volume, there are 2-5 glass fiber meshes per cubic centimeter.

3. The production process of the protective tube with two-component insulating adhesive according to claim 2, characterized in that: The catalyst in the second component is dibutyltin dilaurate, the accelerator is γ-aminopropyltriethoxysilane, and the adhesion promoter is N-β-aminoethyl-γ-aminopropyltrimethoxysilane.

4. The production process of the protective tube with two-component insulating adhesive according to claim 3 is characterized in that: In step (5), the method for producing a glass fiber mesh, (1) When drawing the glass fiber used as one of the warp and weft threads, the glass fiber is in a molten state and passes through a space where ferroferric oxide powder dust is floating in the air, and is bonded with soft magnetic powder, the particle size of which is 0.05-0.20 μm; (2) When drawing the other type of glass fiber used as the warp and weft, the molten state is passed through a space where ferroferric oxide powder dust is floating in the air, and graphite powder is bonded to the fiber. The particles of the graphite powder are 6-10 μm.

5. The production process of the protective tube with two-component insulating adhesive according to claim 4, characterized in that: 1%-2% of graphene oxide-europium oxide composite is added to the first component of the fixing glue.

6. The production process of the protective tube with two-component insulating adhesive according to claim 5, characterized in that: In step (6), the fixing glue is auxiliary-cured by an auxiliary curing device; the auxiliary curing device includes an electromagnet, an oscillating circuit is connected to the electromagnet to generate a magnetic field with periodic direction changes, the electromagnet is close to the fixing glue, and the soft magnetic powder on the glass fiber can vibrate in the alternating magnetic field to expel the air in the curing glue, and the vibration also promotes the tightness of the glass fiber and the fixing glue; The auxiliary curing device also includes an electromagnetic emitter, and the europium oxide in the graphene oxide-europium oxide composite is excited to fluoresce by the electromagnetic field generated by the electromagnetic emitter; The auxiliary curing equipment also includes a microwave heating device, which generates an alternating magnetic field. The glass fiber is bonded with soft magnetic powder, which has soft magnetic properties and can introduce the magnetic field deep into the fluid glue to form a relatively uniform magnetic field distribution in the fluid glue, thereby making the fluid glue with conductive properties heat relatively evenly.

7. The production process of the protective tube with two-component insulating adhesive according to claim 6, characterized in that: When europium oxide is excited to fluoresce by the electromagnetic field generated by the electromagnetic transmitter, the first component undergoes cross-linking under the fluorescence irradiation to form a cured structure. The coating surface of the first component undergoes a condensation reaction with the second component to form a coating layer. This fixing adhesive that combines photocuring and chemical condensation can improve the performance and durability of the cured fixing adhesive.

8. The production process of the protective tube with two-component insulating adhesive according to claim 7, characterized in that: The heteroaramid braided layer and the carbon fiber braided layer are heated and cured by a microwave heating device.

9. The production process of the protective tube with two-component insulating adhesive according to claim 1, characterized in that: In step (2), the fiber braiding angle of the carbon fiber braided layer is different from the fiber braiding angle of the heteroaramid braided layer; ensuring that each layer of material of the protective tube is evenly stressed during the production process, avoiding the generation of stress concentration areas, thereby improving the overall performance of the casing.

Citation Information

Cited By

  • Power cable insulation protection tube structure enhancement and damage repair process

    CN119253503A

  • Power Cable Insulation Protection Pipe Structure Enhancement and Damage Repair Process

    CN119253503B